Inverse initial-value problem in the spaces of Bessel potentials - Boyko, P.; Lopushansky, A.; Lopushanska, H. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.95 We study the inverse problem of reconstruction (in the entire scale of spaces of Bessel potentials) of the initial values of the solution to a time-space fractional diffusion equation with a time-integral additional condition. We also establish sufficient conditions for the unique solvability of the inverse problem.